“Civil War inside my Body”. Two Narratives of Dying in Contemporary Anglophone Film” - Fernández Morales, Marta (Miscelánea: A Journal of English and American Studies, 2007)
After the sexual revolution of the 1970s, death is the ultimate taboo in contemporary Western societies. It is present, yet silenced in our everyday lives. As a theme in culture, “the end” has been a leitmotiv for centuries. However, the process of dying is something feared and under-represented even today. Over the last two decades, books and films have appeared opening new debates on death and dying, palliative care, and euthanasia. This article analyzes two examples of female narratives of dying in the light of the theories of illness and death specialists like David Morris, Ira Byock or Susan Sontag, with her classic Illness as Metaphor.Wit offers an ironic and profound insight on the dying process of Vivian Bearing, a professor of metaphysical poetry. Diagnosed with ovarian cancer in a terminal stage, she re-defines her illness as an intellectual challenge, facing it as a battle for knowledge.The protagonist of My Life Without Me is totally different from Bearing: without a formal education, she lives in a trailer with her husband and daughters. Upon being diagnosed with metastasized ovarian cancer, she decides to make a list of “things to do” and she tries to prepare everything for “her life” to continue without her.
Keywords: Death and dying; Sick role; Body politics; Biomedical model; Contemporary film